Pengaruh Kepercayaan Konsumen, Kualitas Pelayanan, Kemudahan Penggunaan Dan Penetapan Harga Terhadap Kepuasan Konsumen Jasa Transportasi Maxim Malang (Studi Kasus MahasiswaUniversitas Islam Malang) - Jeka Sri Vita Sari; Rois Arifin; Kartika Rose Rachmadi (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract  The aim of this study is to determine how customer satisfaction with transportation services at Maxim Malang is influenced by factors such as customer trust, service quality, usability, and cost. Students from the Islamic University of Malang became the study target group. The sample was taken using the Malhotra methodology, resulting in a final response rate of 100. Purposive sampling is the procedure used to select the sample. Multiple linear regression is the data analysis method used in this study, assisted by the SPSS for Windows program. The findings of the investigation are: 1. Customer trust, service quality, ease of use, and price are independent factors, while consumer happiness is the dependent variable. The findings show that customer satisfaction is significantly influenced by consumer trust, service quality, usability, and cost. Keywords: Consumer Trust, Service Quality, Easy of Use and Pricing, Consumer Happines